PRINSIP KETERBUKAAN DALAM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA: ANALISIS NORMATIF PUTUSAN MAHKAMAH KONSTITUSI - Fatma Faisal; La Ode Muhammad Muskur; Rahmatullah (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
The principle of openness constitutes a fundamental foundation of a democratic state governed by the rule of law, requiring that the law-making process be conducted in a transparent and participatory manner. In Indonesia’s constitutional system, this principle derives its constitutional legitimacy from the 1945 Constitution of the Republic of Indonesia and is further regulated by Law Number 12 of 2011 on the Formation of Laws and Regulations. However, legislative practice reveals a tendency to disregard the principle of openness, leading to formal judicial review before the Constitutional Court. This article aims to normatively analyze the Constitutional Court’s interpretation of the principle of openness in the law-making process. The research employs a normative legal method using statutory and case approaches. The findings indicate that the Constitutional Court plays a strategic role in strengthening openness as part of constitutional democracy, although its implementation continues to face challenges in legislative practice. This article contributes to the development of formal judicial review studies by affirming openness as a substantive constitutional standard in law-making, while also enriching the discourse on formal review by elaborating openness as a substantive constitutional parameter and deepening the concept of meaningful public participation in the context of judicial control over the legislative process in Indonesia.